Valuable predictors of gestational diabetes mellitus in infertile Chinese women with polycystic ovary syndrome: a prospective cohort study - Hexia Xia; Ruixiu Zhang; Xiaoli Sun; Lu Wang; Wei Zhang (Taylor & Francis Group, 2017)
Objective: This study aimed to explore valuable preconception predictors of gestational diabetes mellitus (GDM) in PCOS patients.Methods: A prospective cohort study enrolling infertile Chinese PCOS women treated with ovulation induction was performed. The endocrine, metabolic and physical features of all the patients were collected before pregnancy and then followed up to 6 weeks after delivery. The prevalence of GDM was determined during 24-28 gestational weeks. Logistic regression analysis and receiver operating characteristic (ROC) curves were applied to explore the risk factors and their predictive value for GDM.Results: A total of 94 infertile PCOS women who got singleton pregnancy by ovulation induction were enrolled in the study. Logistic regression analysis showed that the preconception insulin under the curve (IAUC) and sex hormone-binding globulin (SHBG) levels were two most significant risk factors for developing GDM (p = 0.014; p = 0.042, respectively). The area of SHBG and IAUC under the ROC curve were 0.806 (p < 0.001) and 0.775 (p = 0.001), respectively. The optimal cutoff values were failed to be calculated because of the limited group size.Conclusions: Low SHBG level and hyperinsulinism were both strongly associated with the development of GDM and might be two valuable predictors in PCOS patients.